A randomized controlled trial on ambulatory blood pressure lowering effect of CPAP in patients with obstructive sleep apnea and nocturnal hypertension. (2nd January 2020) - Chen, Qi; Cheng, Yi-Bang; Shen, Meng; Yin, Bin; Yi, Hua-Hua; Feng, Jing; Li, Min; Li, Qing-Yun; Li, Yan; Wang, Ji-Guang
Abstract: Objective: In a randomised controlled trial, we investigated the blood pressure (BP) lowering effect of continuous positive airway pressure (CPAP) in patients with moderate-severe obstructive sleep apnoea syndrome (OSAS, an apnoea-hypopnoea index, AHI of 15 or higher) and nocturnal hypertension (night-time systolic/diastolic BP ≥120/70 mmHg). Methods: Sixty patients were randomly assigned to CPAP or sham CPAP, while maintaining their antihypertensive treatment. Ambulatory BP monitoring was performed at baseline (first run-in visit) and the end of follow-up. Clinic and home BP were measured at baseline and each of the monthly follow-up visits. Results: Of the 60 patients, 47 completed the 3-month study. CPAP ( n = 26), compared with sham CPAP ( n = 21), slightly and non-significantly reduced 24-h systolic/diastolic BP by −2.8/−2.5 mmHg ( p ≥ 0.27), with a slightly greater between-group difference in the daytime (−4.0/−2.8 mmHg, p ≥ 0.29) than night-time (−0.2/−1.5 mmHg, p ≥ 0.50). The CPAP treatment did not significantly influence clinic or home BP during follow-up ( p ≥ 0.27). Nonetheless, simple and partial correlation analyses showed that the ambulatory BP lowering effect was dependent on the daytime pulse rate at baseline ( r ≥ 0.47, p ≤ 0.01). In patients with a daytime pulse rate greater than 85 beats/min, the mean changes in daytime systolic BP were significantly greater in the CPAP ( n = 10) than sham CPAP group ( n = 11), with a between-group mean difference of −10.1 mmHg ( p = 0.048). Conclusions: The CPAP treatment did not show significant ambulatory BP lowering effect in patients with moderate-severe OSAS and nocturnal hypertension. However, it may be effective in lowering daytime BP in patients with a faster pulse rate.